Chapter Temi occidentali e loro variazioni russe nelle narrazioni letterarie sul Gulag: Ju. Margolin, V. Šalamov, Ju. Dombrovskij, A. Solženicyn - Jurgenson, Luba (Biblioteca di Studi Slavistici, 2017)
Testimonies about the Gulag use several recurring motives. Inspired by narratives of Western culture and their Russian counterparts such as hell or the fragmented body, these motives constitute a metatext on the rupture that the experience of the camp represents both in the life of the prisoner and in the "great text" of culture.